Lapatinib Activates the Kelch-Like ECH-Associated Protein 1-Nuclear Factor Erythroid 2-Related Factor 2 Pathway in HepG2 Cells - Roos, Noëmi Johanna; Aliu, Diell; Bouitbir, Jamal; Krähenbühl, Stephan (Frontiers in Pharmacology, 2020)
The receptor tyrosine kinase inhibitor lapatinib, indicated to treat patients with HER2-positive breast cancer in combination with capecitabine, can cause severe hepatotoxicity. Lapatinib is further associated with mitochondrial toxicity and accumulation of reactive oxygen species. The effect of lapatinib on the Keap1-Nrf2 pathway, the major cellular defense pathway against oxidative stress, has so far not been studied in detail. In the present study, we show that lapatinib (2-20 µM) activates the Keap1-Nrf2 pathway in HepG2 cells, a hepatocellular carcinoma-derived cell line, in a concentration-dependent manner upon 24 h of treatment. Lapatinib stabilized the transcription factor Nrf2 at concentrations ≥5 µM and caused its nuclear translocation. Well-established Nrf2 regulated genes (Nqo1, Gsta1, Gclc, and Gclm) were upregulated at lapatinib concentrations ≥10 µM. Furthermore, cellular and mitochondrial GSH levels increased starting at 10 µM lapatinib. As a marker of oxidative stress, cellular GSSG significantly increased at 10 µM and 20 µM lapatinib. Furthermore, the gene expression of mitochondrial Glrx2 and SOD2 were increased upon lapatinib treatment, which was also observed for the mitochondrial SOD2 protein content. In conclusion, lapatinib treatment for 24 h activated the Keap1-Nrf2 pathway in HepG2 cells starting at 10 μM, which is a clinically relevant concentration. As a consequence, treatment with lapatinib increased the mRNA and protein expression of antioxidative and other cytoprotective genes and induced GSH synthesis, but these measures could not completely block the oxidative stress associated with lapatinib.